2003
DOI: 10.1063/1.1557713
|View full text |Cite
|
Sign up to set email alerts
|

High linear density in perpendicular recording

Abstract: Two kinds of perpendicular oxide media are compared with a conventional, boron-alloy media. Using an integrated, 245 nm wide, single-pole, high-Bsat writer with trapezoidal write pole, a linear density of 760 kfci at a BER of 10−5 was achieved at the ID radius of an oxide disk at 5400 RPM. MFM images of written tracks show higher-quality transitions up to a higher linear density on the oxide media. Furthermore, transitions on the B-alloy media exhibit a high degree of curvature. Finally, room temperature measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Such media combine the ideal magnetic properties of superlattices (high coercivity, large negative nucleation field) with the low-noise properties of thin-film media (small grain size and grain size uniformity) [6a-c]. They became more widely available in 2002 when their potential for highdensity PMR was recognized [7].…”
Section: Mediamentioning
confidence: 99%
“…Such media combine the ideal magnetic properties of superlattices (high coercivity, large negative nucleation field) with the low-noise properties of thin-film media (small grain size and grain size uniformity) [6a-c]. They became more widely available in 2002 when their potential for highdensity PMR was recognized [7].…”
Section: Mediamentioning
confidence: 99%
“…However, this resolution is not sufficient for nanomagnetic devices like spin electronic devices, perpendicular magnetic storage media, and magnetic random access memories [10][11][12]. In the memories the minimal bit length is expected to be well below 20 nm [13], so improved spatial resolution in MFM technique below 10 nm is clearly needed.…”
Section: Introductionmentioning
confidence: 98%
“…The higher coercivity makes the recorded magnetization thermally more stable, but also means that the media resists reacting to the recording fields generated from the master disk as well as the recording head. Research of high-density recording for areal densities over 100 Gbits/in have been reported using perpendicular recording media with high coercivities ranging from 4500 to 6000 Oe [5], [6].…”
Section: Introductionmentioning
confidence: 99%